Preoperative diagnosis of pelvic actinomycosis by clinical cytology - Matsuda K; Nakajima H; Khan KN; Tanigawa T; Hamaguchi D; Kitajima M; Hiraki K; Moriyama S; Masuzaki H (Dove Medical Press, 2012)
Katsuya Matsuda,1 Hisayoshi Nakajima,2 Khaleque N Khan,1 Terumi Tanigawa,1 Daisuke Hamaguchi,1 Michio Kitajima,1 Koichi Hiraki,1 Shingo Moriyama,3 Hideaki Masuzaki11Department of Obstetrics and Gynecology, Nagasaki University Graduate School of Biomedical Sciences, 2Department of Health Sciences, Nagasaki University Graduate School of Biomedical Sciences, 3Shimabara Maternity Clinic, Nagasaki, JapanBackground: The purpose of this work was to investigate whether clinical cytology could be useful in the preoperative diagnosis of pelvic actinomycosis.Methods: This study involved the prospective collection of samples derived from the endometrium and the uterine cervix, and retrospective data analysis. Nine patients with clinically diagnosed pelvic actinomycosis were enrolled. The clinical and hematological characteristics of patients were recorded, and detection of actinomyces was performed by cytology, pathology, and bacteriological culture of samples and by imprint intrauterine contraceptive device (IUD) cytology.Results: The detection rate of actinomyces was 77.7% by combined cervical and endometrial cytology, 50.0% by pathology, and 11.1% by bacterial culture.Conclusion: The higher detection rate of actinomyces by cytology than by pathology or bacteriology suggests that careful cytological examination may be clinically useful in the preoperative diagnosis of pelvic actinomycosis.Keywords: actinomycosis, cytology, pathology, intrauterine contraceptive device, pelvic inflammatory disease